2015
DOI: 10.1039/c5ta03471j
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene oxide)-based electrolytes for lithium-ion batteries

Abstract: This article reviews the PEO-based electrolytes for lithium-ion batteries.Poly(ethylene oxide) (PEO) based materials are widely considered as promising candidates of polymer hosts in solid-state electrolytes for high energy density secondary lithium batteries. They have several specific advantages such as high safety, easy fabrication, low cost, high energy density, good electrochemical stability, and excellent compatibility with lithium salt. However, the typical linear PEO does not reach the production requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
1,428
1
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,720 publications
(1,517 citation statements)
references
References 629 publications
15
1,428
1
6
Order By: Relevance
“…The cathode materials used in batteries are vanadium oxide, molybdenum sulfide, molybdenum oxide, manganese oxide, silicates, LiCoO 2 , LiFePO 4 , LiMn 2 O 4 etc. [1][2][3][4][5]. The different types of electrolyte materials based on biopolymer are studied briefly in this review.…”
Section: Fabrication Of a Batterymentioning
confidence: 99%
See 4 more Smart Citations
“…The cathode materials used in batteries are vanadium oxide, molybdenum sulfide, molybdenum oxide, manganese oxide, silicates, LiCoO 2 , LiFePO 4 , LiMn 2 O 4 etc. [1][2][3][4][5]. The different types of electrolyte materials based on biopolymer are studied briefly in this review.…”
Section: Fabrication Of a Batterymentioning
confidence: 99%
“…It is also identified that Li-ion batteries (LIBs) are the preferred system for electric vehicles, grid energies and flexible electronic devices due to their high energy and power density [4]. Particularly, flexible and wearable electronics are expected to increase an exceptional importance in the future as energy storage devices.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations